Multi-Criteria impact assessment of MVML in performance of interactive systems for people with disabilities - Salim, S.S.; Asemi, A.; Champiri, Z.D.; Shahamiri, S.R. (2014)
The impact assessment of MVML with different criteria is a primary step in the optimisation of Interactive Systems for People with Disabilities (DPISs). This study aims to assess the impact of MVML in comparison with other active learning methods based on multiple criteria. We apply a model of mathematical fuzzy Multi Criteria Decision Making (MCDM) for evaluation of active learning methods. We determine the critical factors that are effective in the performance of interactive systems for people with disabilities. An expert’s judgment is used to compare the methods with each other for all criteria. The fuzzy set theory is applied to fuzzify the human judgments. The impact assessment of active learning methods is conducted by calculating the eigenvector from pairwise comparison matrixes. We found “Usefulness”, “Feedback Adequacy”, “Error Handling Adequacy”, “Modality Appropriateness” and “System Response” are critical factors. The results show that MVML has the highest impact in usefulness and feedback adequacy. The overall impact of active learning methods illustrates the high impact of SVML in comparison with other methods for applications in DPISs.